UPAYA PENINGKATAN PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK DENGAN BERMAIN LOMPAT DAN LONCAT PADA SISWA KELAS V SD INPRES TIKATUKANG KECAMATAN ADONARA KABUPATEN FLORES TIMUR - Mangu, Kosmas Ola (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The background of the conduct of this study is based on the achievement of squat jumps in particular and athletic sports in general that do not show progress. The author realizes that this is important so that through discussions at the KKG level, almost all schools complain about the disinterest of students in this one sport. Therefore the author feels compelled to make a classroom action research to be able to find a solution so that the deterioration of athletic sports, especially the long jump number can be returned. The method used in this study is a class action research method wherein the jump and jump patterns are packaged in an exciting game, so that students are motivated in participating in this learning material. For the sample population in this study were all fifth grade students in SD Inpres Tikatukang in the academic year 2017/2018. The research procedures include: Planning, Implementation, observation and reflection. Through the application of the jump and jump approach it was observed that there was an increase in student activity from cycle I to cycle II, where through observation from the active category it became very active, the good category became very good, from discipline to very disciplined. It was illustrated that by jumping and jumping students experienced an increase in learning achievement, namely 100% of children in the good category (B). While the long jump with a prefix of 95% of children is in a good category. 5% enough category. The attitude of drifting 85% of children in good category, 15% of children in sufficient category, while attitude to landing, 89% in good category and 11% in sufficient category